Associations Between Maternal Exposure to Child Abuse, Preterm Birth, and Very Preterm Birth in Young, Nulliparous Women - Cammack, Alison L. (Matern Child Health J, 2019)
OBJECTIVES: Preterm birth (PTB) is a leading cause of infant morbidity and mortality. One goal of Healthy People 2020 is to understand the role of preconception lifecourse exposures in relation to pregnancy outcomes, including PTB. The objective of this study was to examine the relationship between maternal exposure to multiple forms of childhood abuse and PTB and very preterm birth (vPTB), utilizing a national, population-based sample. METHODS: This study utilized retrospective self-reported maternal exposure to parent/adult caregiver perpetrated emotional, physical, and sexual abuse; non-parental/adult caregiver perpetrated sexual abuse; and history of PTB and vPTB in the National Longitudinal Study of Adolescent to Adult Health. The cross-sectional analytic study population consisted of first deliveries to 4,181 nulliparous women (mean age at time of delivery= 21.7 years). RESULTS: With one exception, we did not observe associations between experiences of child abuse and the likelihood of PTB or vPTB. Only sexual abuse, accompanied by physical force and perpetrated by a non-parent/adult caregiver, was associated with an increased odds of vPTB (aOR= 1.94 (95% CI:1.10, 3.44)), particularly in women for whom abuse began after age 9 (aOR=2.32 (95% CI: 1.25, 4.28)). CONCLUSIONS FOR PRACTICE: The relationship between maternal exposure to child abuse and PTB may be limited to specific abuse and PTB subtypes, namely parent/caregiver perpetrated sexual abuse by force and vPTB. Future studies should also examine possible effect modifiers, such as maternal age and resilience, which may have the potential to inform interventions that can mitigate effects of maternal early life adversity.